MATLAB / SIMULINK MODELING OF THE OPERATION OF ONE ELECTRIC VEHICLE IN DIFFERENT DRIVE CYCLES (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The present paper aims to improve the methods of dynamic design of electric vehicles, by creating simulation models in Simulink. The models are represented by simulation schemes that consist of blocks of mathematical operators, interconnected based on mathematical calculation formulas. The initial input sizes, specified in Table 1, can be easily modified, giving the possibility to obtain several models for different design ideas. The results of the simulations are materialized in graphical diagrams and provide virtual time data on vehicle speed, acceleration, engine torque, wheel power, energy consumed and distance traveled. In the first simulation scheme, the input variable is represented by a motor torque generator, with values ​​between 0-132 Nm. In the second simulation scheme, the input variable is speed, according to the ECE-15 urban cycle scenario.
Keywords: ELECTRIC VEHICLE; DRIVE CYCLES; MODELING